Contribution to Investigation of the Influence of Chemical Composition on Machinability of Superalloy Nimonic 80A. (2015) - Sunulahpasic, R.; Hadzalic, M.; Oruc, M.; Begovic, E.
Abstract: Nimonic 80A is a material used in extreme conditions in the automotive industry and everywhere where elements work in extreme environment (high temperature and aggressive environment). This is an alloy which is very difficult to process. The aim of this paper is research in field of machinability of superalloy Nimonic 80A. Experimental investigations with defined cutting conditions will determine the influence of the chemical composition of superalloy Nimonic 80A on the machinability.